Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

La Bolduc en tournée : un patrimoine matériel unique - Boulay, Vicky (Magazine Gaspésie, 2014)
An article from Magazine Gaspésie, on Érudit.
Publisher: Musée de la Gaspésie

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Les Daraîche, la famille royale du country - Dumas, Carmel (Magazine Gaspésie, 2014)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

Mad Je Deviendrai : Les divas dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)